Knoxdaviesia capensis: dispersal ecology and population genetics of a flower-associated fungus. (April 2017) - Aylward, Janneke; Dreyer, Léanne L.; Laas, Tessa; Smit, Lelani; Roets, Francois
Abstract: Protea -associated fungi are dispersed between flower heads by mites, beetles and possibly birds. For the ophiostomatoid fungus, Knoxdaviesia proteae, these vectors offer regular dispersal between distant floral hosts. Unlike K. proteae, Knoxdaviesia capensis occupies multiple Protea host species. In this study, we aimed to determine whether the generalist K. capensis shares the long-distance dispersal pattern with specialist K. proteae and whether it moves freely between different host species. We evaluated the genetic structure of K. capensis from five populations of a wide-spread host and between sympatric hosts. Twelve K. capensis -specific microsatellite markers were developed and applied to 90 individuals. K. capensis showed high genetic diversity and almost maximal genotypic diversity. All populations were poorly differentiated, indicating the presence of long-distance dispersal. No differentiation could be detected between sympatric host populations, suggesting free dispersal between different hosts. This implies that the beetle and bird vectors that pollinate Protea species show the same non-specific movement. Highlights: Twelve microsatellite markers specific to Knoxdaviesia capensis were developed. High gene and genotypic diversity was observed in nine K. capensis populations. Populations collected from a widespread Protea host were poorly differentiated. Dispersal between different sympatric host species appears to be unhindered. By implication, K. capensis vectors do not discriminate between Protea host species.